Advances in accounting education : teaching and curriculum innovations - Calderon, Thomas G. (Emerald Publishing Limited, 2019)
Advances in Accounting Education is a refereed, academic research publication whose purpose is to help meet the needs of faculty members and administrators who are interested in ways to improve teaching, learning and curriculum development in the accounting area at the college and university level. We publish thoughtful, well-developed articles that are readable, relevant, and reliable. Articles may be either empirical or non-empirical and should emphasize innovative approaches that inform faculty and administrators as they seek to improve their classrooms, curricula and programs.Volume 23 consists of three themes: (1) Capacity Building and Program Leadership, (2) Classroom Innovation and Pedagogy, and (3) Engagement with Professionals Through Advisory Councils.Theme 1, Capacity Building and Program Leadership, include articles that focus on innovation in accounting doctoral programs, roles and professional development opportunities of accounting program leaders, the interaction of gender and performance shortly after junior college students transfer to a four-year college, and the diffusion of data analytics in the accounting curriculum.Theme 2, Classroom Innovation and Pedagogy, consists of a class exercise on accounting for stock option modifications and option service and performance conditions, student group work across geographical and cultural borders, and the use of publicized-data breach cases to incorporate cybersecurity into upper-level accounting courses.Theme 3, Engagement with Professionals Through Advisory Councils, explores ways in which accounting programs might leverage their advisory councils (boards) to improve their curricula and strengthen opportunities for student success. The first article in Theme 3 reports the result of a survey that explores opportunities for interaction between the accounting academy and the profession through advisory councils. This is followed by articles that discuss the use of advisory councils to (a) improve the master's in accountancy curriculum and (b) serve as a catalyst for improving the ethical reasoning skills of accounting students and accounting professionals.In total, this volume includes 10 peer reviewed articles that make significant contributions to teaching, learning, curricula and programs, and faculty development matters in accounting.
Includes index.
Keywords: Accounting -- Study and teaching (Higher); Educational innovations.; Business & Economics -- Accounting -- General.; Accounting.; elektronické knihy; electronic books